Structural Rhinoplasty through the Endonasal Approach - Shah, Anil; Nnabue, Onyekachi Ezinna (Facial Plastic Surgery, 2025)
Structural endonasal rhinoplasty, unlike traditional reductive rhinoplasty, achieves aesthetic and functional objectives while maintaining key structural anatomical elements and minimizing complications.Previously, rhinoplasty was performed using primarily reductive techniques that frequently led to poor functional and cosmetic consequences.Pertinent nasal framework anatomy is reviewed in select highlighted cases.Preferred tools/technology are reviewed for each procedure, including the use of ultrasonic devices.Indications for each endonasal technique are systematically outlined.The most common techniques are reviewed: dorsal hump reduction, spreader graft placement, alar batten and rim grafts, and columellar strut, and caudal extension grafts.Endonasal rhinoplasty allows for reduced postoperative swelling, loss of nasal tip support, as well as decreased scar tissue/contracture formation.Structural endonasal techniques continue to evolve and become more refined with studies demonstrating cosmetic and functional outcomes similar to that of open surgery while achieving less operating time, postoperative complications, and long-term complications. As a result, structural endonasal rhinoplasty is an important surgical principle and approach for the modern rhinoplasty surgeon.
Keywords: structural rhinoplasty; minimally invasive; endonasal approach; preservation rhinoplasty